Collision Between the Own and the Foreign in the Short Story „Die Ferne ist nah genug“ (“The Faraway Land is Close Enough“) by Siegfried Lenz - Barniškienė, Sigita (Literatūra, 2016)
This article is grounded in Hugo Dyserinck’s, a German comparatist’s idea that contemporary imagology can be likened to “European Studies”, as it examines self- and hetero-stereotypes of nations. Another German imagologist’s, Manfred Beller’s, statement that two nations can be often compared by the way of antithetical argument (the Spectant evaluates the Spected) is equally important: the critique of the other nation inspires the positive evaluation of one’s own nation and vice versa – negative opinion about one’s own nation results in positive evaluation of the Other. In this article the philosophical ideas by Bernhard Waldenfels and Hamid Reza Yousefi about the types of the Other were explicated and applied in the interpretation of the Short Story “The Faraway Land is Close Enough” by Siegfried Lenz. In this paper, the point of view of two German boys on the harsh reality of the Lithuanian postwar period is analyzed. The fourteen-year-old boys leave Kaliningrad, occupied by the Russian army, where starvation and compulsion reign, and travel by train to Lithuania. They end up there, begging for food from local peasants. In order to survive, they are forced to cross many moral boundaries, important during the time of peace. The author mentions the stereotypical image of Lithuania, characteristic of Germans before World War Two: the beauty of the Nemunas river, meadows and forests, or endless crop fields. The short story presents an interesting description of the locals: broad-faced and sweating during the harvest season. The text provides information about kind-heartedness of local people, their diligence and skills in trading – they export eggs, butter and meat to Germany. The two boys face a different reality in this country, which is now under occupation of the Soviet Army. The Russian Militsiya arrests the boys, and makes them go back to Kaliningrad; however, they manage to stay in Lithuania, continue begging and even meet Lithuanian partisans in the forest. The boys master Lithuanian and Russian in four years. One of them is found dead in the forest, but the other one goes back to Germany, where he often feels nostalgia for Lithuania. In this short story, the collision between the Own and the Foreign is evident and even emphasized because of the war, occupation of Lithuania, suffering and fear of people. However, the author manages to keep the balance while depicting the painful experiences of the two boys in Lithuania: the cruelty does not outweigh the kindness of people. One of the boys stays alive and misses the foreign country – Lithuania – even after returning back home. It shows the cruel, but, at the same time, positive balance between loss and survival.